Investigating the “Flow” Experience: Key Conceptual and Operational Issues - Abuhamdeh, Sami (Frontiers in Psychology, 2020)
The “flow” experience (Csikszentmihalyi, 1975) has been the focus of a large body of empirical work spanning more than four decades. Nevertheless, advancement in understanding–beyond what Csikszentmihalyi uncovered during his initial breakthrough in 1975–has been modest. In this paper, it is argued that progress within the field of flow has been hampered by a lack of consensual operationalization of flow, which to an extent reflects underlying confusion regarding what flow actually is. After reviewing the many different ways in which flow has been operationalized in the literature during the past five years, three specific points of inconsistency are highlighted: 1) inconsistences in operationalizing flow as a continuous versus discrete construct, 2) inconsistencies in operationalizing flow as inherently enjoyable (i.e. autotelic) or not, and 3) inconsistencies in operationalizing flow as dependent on versus distinct from the perceived task characteristics proposed to elicit it (i.e. the conditions/antecedents). The author argues that, for the sake of conceptual intelligibility, flow should be conceptualized in a manner consistent with Csikszentmihalyi’s conceptualization – as a discrete, highly enjoyable, “optimal” state of consciousness, and that this state should be operationalized independent of the conditions proposed to elicit it. He suggests that more mundane, “sub-optimal” experiences are best conceived and operationalized as variations in intrinsically-motivating task involvement rather than variations in “flow.” Additional ways to achieve greater conceptual and operational consistency within the field are suggested.